Effectiveness of Educational Intervention Regarding Cervical Cancer among Female Teachers in Government Schools, Jhapa - Thapa, Asmita; Rana Thapa, Muna; Darshandhari Kapali, Gayetri (Journal of Nursing Education of Nepal, 2024)
Introduction: Cervical cancer is the leading cause of cancer mortality among women in developing countries. Educational interventions on cervical cancer can decrease the resultant morbidity and mortality. Increasing knowledge on teachers can lead to higher rates of cervical screening and vaccination, both personally and through advocacy. Female teachers not only serve as educators but also act as community influencers and role models for students and other women in society. The aim of this study was to find out the effectiveness of educational intervention regarding knowledge on cervical cancer among female teachers in government schools.Methods: Pre-experimental one group pretest-post test design was carried out on 105 female teachers from government schools of Gaurigunj rural municipality, Jhapa, Nepal by using non-probability purposive sampling. Pretest knowledge was assessed by using structured self-administered questionnaire. The educational intervention package was developed from literature review and guidelines. After four weeks, post test was conducted on the same participants using same instrument used in pretest. Descriptive and inferential statistics; wilcoxon signed rank test was computed for p-value.Results: This study revealed that more than two third (69.5%) of the respondents had poor knowledge in the pre-intervention phase and almost all (92.4%) of the respondents had good knowledge in the post-intervention phase. There was a significant improvement in median score and range from 41.86 (34.88-51.16) to 88.37 (86.05-90.70) respectively (p
Keywords: Cervical cancer; educational intervention; knowledge